Satellite DNA sequence content of polylysine-titratable and nuclease-resistant fractions of mouse liver hepatoma chromatin. - Duerksen, J D (1976)
Micrococcal nuclease digestion of mouse TLT liver hepatoma chromatin proceeds rapidly to the point where approximately 35% of the DNA is recoverable by centrifugation of the chromatin DNA through 3M CsCl. The satellite DNA sequence content of this recoverable DNA is the same as whole chromatin DNA (10%). The 11s (penultimate digestion product) monomer, as well as intermediate multiples and relatively undigested large chromatin segments are separable on steep hlycerol gradients. The DNA isolated from these fractions also contains the normal 10% satellite DNA content. Progressive polylysine titration of chromatin followed by nuclease digestion gives anomalous recoveries of DNA but, nonetheless, the satellite sequence content titration of chromatin, followed by pronase and then nuclease digestion, again gave recoverable DNA with a satellite sequence content of 10%. These results are discussed in terms of the conclusion that nucleosome (or upsilon-body) structures are distributed in a random fashion over the genome.